Adpositiot suomen kieliopeissa 1600-luvulta 1800-luvun loppuun - Merimaa, Heidi (Virittäjä, 2004)
Adpositions in old Finnish grammars (1600-1900) (englanti) 1/2004 (108) Adpositions in old Finnish grammars (1600-1900) Adpositions (i.e. prepositions and postpositions) are a word class that is difficult to delimit, because the same word form can also appear as an adverb, a normal inflectional form of a noun, or a verb. Adpositions are an open category. They are established through the grammaticalisation of nominals, adverbs and verbs. In old Finnish grammars, the boundary with adverbs and nominal inflectional forms was blurred, and a few words that are nowadays classified as adverbs were counted as adpositions, such as ulkona outdoors, outside. Adpositions are treated in a similar manner in the old Finnish grammars. They define adpositions and list the most common of them. Differences between the grammars lie especially in the extent to which adpositions are discussed. This may take up more than ten pages, whereas in school grammars, in particular, adpositions are dismissed in just a few lines. Individual adpositions are not discussed in much detail in the grammars. Besides the meaning and the root, most grammars explain the case forms in which adpositions can appear, and the case form that must be used for the nominal of the adposition. Examples are sometimes given of the use of adpositions. The grammars differ slightly in their view of the correct case form for the nominal of the adposition, and in whether a particular adposition is considered a preposition or a postposition, or both. The adpositions given in the earliest grammars are discussed in most of the later published grammars. The earlier an adposition appeared in a grammar, the more likely it would appear in subsequent grammars, too. Strahlmann (1816) and Becker (1824) brought the greatest number of new adpositions to Finnish grammars. Conclusions about adposition usage in the actual written language of the day cannot safely be made on the basis of old grammars, however, because they do not list all the adpositions that appeared in the written language, and some were erroneously considered to be only prepositions or postpositions. Neither do the old grammars include all the adpositions in use today, partly because some of them were not grammaticalised until later on. Heidi Merimaa